2019
DOI: 10.12740/pp/81104
|View full text |Cite
|
Sign up to set email alerts
|

Errorless Learning as a method of neuropsychological rehabilitation of individuals suffering from dementia in the course of Alzheimer’s disease

Abstract: W niniejszym artykule omówiono możliwości stosowania strategii rehabilitacyjnej znanej pod nazwą bezbłędnego uczenia się (ang. errorless learning, EL) u pacjentów z chorobą Alzheimera. Autorzy przedstawiają zagadnienie w kontekście stanu wiedzy o efektywności oddziaływań neuropsychologicznych u pacjentów cierpiących na AD. Zarysowana jest historia powstania terapii metodą uczenia się bezbłędnego oraz startegie i techniki stosowane w jej obrębie. Wykazane jest nowatorstwo metodologiczne tego podejścia, które, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…These principles involve external cue usage, reliance on implicit memory, guided repetition, and progression from simple to complex. 17,18 It is recommended that activities utilize implicit, automatic, and unconscious cognitive memory processes for persons with severe dementia, to capitalize on the remaining cognitive abilities for those with moderate dementia, and to strengthen the retained abilities and promote the exercise of cognition for those with mild dementia. 24,32,33 The findings also indicated that older adults with dementia may experience difficulty in carrying out the activities required by a majority of game apps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These principles involve external cue usage, reliance on implicit memory, guided repetition, and progression from simple to complex. 17,18 It is recommended that activities utilize implicit, automatic, and unconscious cognitive memory processes for persons with severe dementia, to capitalize on the remaining cognitive abilities for those with moderate dementia, and to strengthen the retained abilities and promote the exercise of cognition for those with mild dementia. 24,32,33 The findings also indicated that older adults with dementia may experience difficulty in carrying out the activities required by a majority of game apps.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is important to incorporate cognitive rehabilitation principles if a game is considered to be therapeutic for an individual with dementia. These principles involve external cue usage, reliance on implicit memory, guided repetition, and progression from simple to complex 17,18 . It is recommended that activities utilize implicit, automatic, and unconscious cognitive memory processes for persons with severe dementia, to capitalize on the remaining cognitive abilities for those with moderate dementia, and to strengthen the retained abilities and promote the exercise of cognition for those with mild dementia 24,32,33 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Le patient doit éviter de deviner la réponse et doit s'abstenir de répondre en cas de doute, et s'il y a des erreurs alors elles doivent être corrigées immédiatement et la bonne réponse sera alors demandée à nouveau. Plusieurs types de stratégies employant l'apprentissage sans erreur sont généralement utilisées en remédiation cognitive [14,15]. Le choix d'une stratégie ou de plusieurs stratégies combinées varie selon le type de population clinique ciblée et le type d'apprentissage visé.…”
Section: Introductionunclassified